Ectopic papillary thyroid carcinoma within a thyroglossal duct cyst: A case report. Issue 48 (December 2017) - Roehlen, Natascha; Takacs, Szilvia; Ebeling, Olaf; Seufert, Jochen; Laubner, Katharina
Abstract: Rationale: Ectopic thyroid carcinoma within a thyroglossal duct cyst (TGDCCa) is an extremely rare entity. Thus, there is no unified appropriate therapeutic strategy, and individual approaches are controversial. Patients concerns: We report the case of a 21-year old woman who underwent Sistrunk procedure for a thyroglossal duct cyst (TGDC). Diagnoses: During histological evaluation of the resected TGDC a papillary thyroid carcinoma was found. Interventions: Due to a tumor size of 1cm and proximity to the surgical border, Sistrunk procedure was extended by total thyroidectomy, followed by radioiodine ablation. Outcomes: Except of minimal follicular hyperplasia, the histological examination of the resected thyroid gland was unsuspicious. Lessons: Therapeutic management of TGDCCa is of interdisciplinary debate due to relative infrequence of the disease and consequently lack of unified therapeutic guidelines. We suggest a personalized therapeutic approach adjusted to individual risk stratification. In young patients with small tumor size and with confirmation of TGDCCa representing the primary tumor, Sistrunk procedure alone may reflect adequate treatment. In all other cases, total thyroidectomy and radioiodine ablation should be evaluated. Overall TGDCCa have an excellent prognosis with a 5-year survival rate of more than 90%.